Knowledge Visualization Centers and University Infographics: International and Domestic Experience - A. V. Makulin; M. I. Korzina (Высшее образование в России)
Infographics as a young science of converting massive volumes of knowledge into concise emergent visualizations, i.e. the methodology that works with transcoded knowledge, has become capable, at the digital stage of its own evolution, to integrate the most diverse fields of knowledge. This is possible due to the advantages that the graphic language provides along with all other ways of expressing and formalizing knowledge. The potentials of infographics for the university environment provide an opportunity to visually operate with vast volumes of knowledge, to search for new interdisciplinary nexus-points and heuristic intersections in the network structure of university science. Along the way, the problems of inventive tasks and the promotion of scientific knowledge are solved through digital infographic visualizations on the Internet, within and between universities. The article develops an idea of socio-epistemological and interdisciplinary potentials of the phenomenon of scientific and philosophical infographics for the sustainable growth of the competitive advantages of the Russian education system. The authors analyze the world and domestic experience in infographics functioning in science, business, management and consider a new project for a domestic university education on creating a knowledge visualization center on the example of a particular university. The authors give the examples of successful international data visualization projects and pay particular attention to the creation of a holistic interdisciplinary catalog of infographics. University digital library can serve as a source of databases and potentials of the visualization center, as a tool for visualizing this data. The authors discuss the possibility of infographic expertise procedure formation as a new methodology for analyzing and improving various program documents, social development programs, business projects, and dissertations. The article makes the case for developing infographic competencies of innovation actors in education, business and public administration.